A Method for Automatic Recording of the Osmotic Fragility of Blood Platelets - Zahavi, J; Danon, D; Dreyfuss, F; Nelken, D (Thrombosis and Haemostasis, 1970)
A method for automatically recording the osmotic fragility of blood platelets, using a Fragiligraph, was developed. Platelet specimens taken from 20 healthy males and 9 females were examined. The mean rate of platelet change and the extent of increase in light transmission (LT) of washed platelets suspended in veronal, Tris, or phosphate buffered saline and dialyzed against water and 0.1% sodium chloride solutions, were analyzed. The recorded curves showed a slow phase lasting 2–74 sec, followed by a phase representing a rapid rate of platelet change in which gradually swelling of the platelets occurred concomitantly with an increase in the LT. This was followed by a third phase of plateau formation. The mean rate of platelet swelling was temperature-dependent, having twice the value at 37° C as at 15° C; the extent (% increase in LT) did not vary with temperature.